Seasonal hotspots of beach litter in the North-East Atlantic linked to aquaculture and river runoff - Rieger, Niclas; Olmedo, Estrella; Thiel, Martin; Salvo, Vanessa Sarah; Honorato-Zimmer, Daniela; Vásquez, Nelson; Turiel, Antonio; Piera, Jaume (Communications Earth & Environment, 2024)
12 pages, 5 figures, supplementary information https://doi.org/10.1038/s43247-024-01913-7.-- Data availability: All data sets utilized in this study are publicly accessible. The OSPAR data set, detailing beach litter information, is available for download at https://beachlitter.ospar.org/survey/export. Data on river discharge for the European Flood Awareness System (EFAS) domain is provided by the Copernicus Climate Data Store (CDS) (https://doi.org/10.24381/cds.9f696a7a). Ocean wave reanalysis data is obtainable from the Copernicus Marine Environmental Monitoring Service (CMEMS) (https://doi.org/10.48670/moi-00022). Data on riverine macroplastic emissions43 are available at https://doi.org/10.17026/dans-xaa-kug9. Production data from wild capture fisheries and aquaculture are available from the Food and Agriculture Organization (FAO) at https://www.fao.org/fishery/en/collection/capture?lang=en and https://www.fao.org/fishery/en/collection/aquaculture?lang=en, respectively. Monthly exports for fish and aquaculture products can be sourced from the European Market Observatory for Fisheries and Aquaculture Products (EUMOFA) at https://eumofa.eu/data. Additionally, the locations of mariculture farms59 are published at https://doi.org/10.5063/F1736PBP, which are partly based on data provided by the European Marine Observation and Data Network (EMODnet), available at https://emodnet.ec.europa.eu/geonetwork/srv/eng/catalog.search#/home. The results of this study are available at https://doi.org/10.6084/m9.figshare.26155156.-- Code availability:In the spirit of transparency, open science, and reproducibility, we have made all scripts available for processing and analyzing the data, as well as for producing the figures used in our study: https://github.com/nicrie/seasonality_ospar Macroplastic pollution is a pervasive global environmental challenge, adversely affecting marine ecosystems, wildlife and human health. Understanding temporal variations is crucial for identifying pollution sources and developing effective ...